Microorganisms Number On X-Ray Cassette - Dartini Dartini; Sugiyanto Sugiyanto; Widi Hidayati (Jurnal Riset Kesehatan, 2014)
X-ray cassette is a light-tight container to cover radiographic film during radiographic examination. Cassette can directly or indirectly contact with the patient’s body. It can be a spreading medium of bacteria from patient to patient, or patient to radiographer. The aims of this study are to determine the number of microorganisms contained in the cassette before and after cleaning, and to know the difference between those two numbers. The study is an observational study with cross-sectional approach. The survey was done to 17 cassettes to measure the number of bacteria using swap method. Then, the data were analyzed using Wilcoxon test. Result shows that the mean of bacteria, fungi, staphylococcus and ALT on cassettes before cleaning was larger than the mean after cleaning the cassette using 70 % alcohol. The Wilcoxon test in bacteria, fungi, staphylococcus and ALT showed ρ = 0.0001, 0.012, 0.0001 , 0.0001 less than 0.05 means that there was a significant difference in the content of bacteria, fungi, staphylococcus and ALT before and after cleaning the cassette using alcohol 70%. Based on these results the cassette should be cleaned regularly every morning to avoid the possible spread of bacteria.